PENERAPAN MODEL PICTURE AND PICTURE DALAM PEMBELAJARAN MENULIS TEKS BIOGRAFI PADA SISWA KELAS X SMA NEGERI 1 SURANENGGALA TAHUN PELAJARAN 2024/2025 - Fitriyana; Muhammad Sholeh; Fithry Muthmainnah (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to determine the effectiveness of the Picture and Picture learning model in improving students’ ability to write biographical texts in Grade X of SMA Negeri 1 Suranenggala during the 2024/2025 academic year. The research was motivated by the low interest of students in reading and writing activities, particularly in learning biographical texts. This problem arises due to the lack of variation in teaching models used by teachers, resulting in monotonous learning activities that fail to foster students’ motivation. Consequently, students’ writing skills remain low, especially in vocabulary mastery, idea organization, and paragraph development. This research employed an experimental method using a pretest-posttest control group design. The research subjects consisted of 22 students from class X-B as the experimental group and 22 students from class X-D as the control group. Data were collected through observation and writing tests (pretest and posttest). The data were analyzed using an independent sample t-test. The results showed that the calculated t-value (2.269) was higher than the critical t-value (1.681), indicating that H₀ was rejected and H₁ was accepted. Therefore, the Picture and Picture model was proven to be effective in enhancing students’ ability to write biographical texts. Furthermore, the observation results revealed an increase in students’ activeness, cooperation, and participation during the learning process.